An Industrial systems study on Tiongson Industries, Inc. - Atienza, Maria Jazmin V.; Erpelo, Michael P.; Galon, Jude Hercules M.; Santos, Michelle P. (College of Engineering, 2001)
Tiongson Industries, Incorporated (TII) is a manufacturing firm producing industrial cans since 1960's. TII produces up to 2000 tons of cans every year. Industrial cans produced are of varying sizes from 1/8th liter to 20 liters. Documentation and interviews allow the proponents of the study to have a glimpse on the company systems and procedures and problems. Kepner and Tregoe's rational management tools are used to identify the concerns of TII. Areas of concern were divided into Purchasing, Warehousing, Production, Transport Operations and Marketing and Sales. Using Streamline Analysis and Pareto Chart Principle, the major problems were identified and these were (1) bottleneck in lithography, (2) lack of warehouse management techniques and (3) lack of scrap disposal policies. Alternatives for bottleneck problem are to invest on a lithograph machine, change the lithograph process and status quo. Using the systems evaluation principles, investing on a lithograph machine would only have an annual cost of PhP 1,635,000 compared to status quo's cost, which is PhP 3,100,000. After factor rating, the buying of a lithograph machine emerges to be the best solution for the said problem. Besides the status quo, the proponents of the study suggest a stock locator system for the company's warehouse management problem. With the present system the percent utilization of TII's warehouse for the first, second and third level is 37%, 75% and 68% respectively. With the presence of a stock locator system the present utilization for each level are 63%, 84% and 74% respectively. A scrap disposal policy is suggested so that there would be a better system in managing wastes. By placing the said policy, an additional profit of PhP 735,000 can easily be traced. Factor rating also provided that this alternative is better by 9 points compared to company's status quo. In analyzing the TII manufacturing and operating systems and application of supply chain management techniques, the study aims to help increase company's profit and improve its systems and procedures.